Influence e-recruitment and recruitment conventional to opportunity get work (studies case on employee in region Jabodetabek) - Purwanti, Purwanti; Hermiati, Novi Fitria (Institute of Computer Science (IOCS), 2024)
The background of this research is to determine the difference between using online employee recruitment methods and conventional recruitment methods on the chances of getting a job for employees in the JABODETABEK area. The research was conducted using quantitative methods. The population in this study is not known with certainty due to the lack of data that is freely accessible in the Jabodetabek area. The sampling technique used in this study uses a probability sampling method by randomly selecting each population to be sampled. Meanwhile, the sampling used in this research used a simple random sampling technique. The samples in this research were obtained from the Lemeshow formula, totaling 96. Data were collected using a questionnaire and analyzed using SMART PLS 4.0. The data analysis techniques used include validity testing, reliability testing, structural equation model testing, PLS-SEM, PLS model evaluation, outer model evaluation and inner model evaluation. This research concludes that online recruitment has an effect on job opportunities and conventional recruitment has no effect on job opportunities